Relationship between skeletal muscle index at the third lumbar vertebra with infection risk and long-term prognosis in patients with acute-on-chronic liver failure - Wang, Juan; Bai, Jinjia; Wang, Huimin; Xu, Guofen; Yao, Ruoyu; Li, Jing; Zhang, Wenrui; Wang, Han; Yao, Jia; Ren, Xiaojing (Frontiers in Nutrition, 2024)
Objective Infection is a major cause of increased mortality in patients with acute-on-chronic liver failure (ACLF). This study aims to examine the potential correlation of the skeletal muscle index at the third lumbar vertebra (L3-SMI) with infections among ACLF patients and to evaluate its impact on the long-term survival. Methods This retrospective study included 126 patients who underwent abdominal computed tomography (CT) and were diagnosed with ACLF at our center between December 2017 and December 2021. L3-SMI was calculated using CT, and the clinical and biochemical data as well as MELD scores were also collected, so as to analyze the relationship between L3-SMI and infections in ACLF patients and the impact on long-term prognosis. Results Of the 126 ACLF patients enrolled, 50 had infections. In the multivariate logistic regression analysis, both L3-SMI [odds ratio (OR) = 0.89, 95% confidence interval (CI) = 0.81 – 0.97, P = 0.011] and hepatic encephalopathy (OR = 8.20, 95% CI = 1.70 – 39.59, P = 0.009) were independently associated with the risk of infection development. The overall survival (OS) estimates were obtained using Kaplan-Meier curves, and it was found that patients in the lowest tertile of L3-SMI had significantly lower 3-month, 6-month, 1-year, and 2-year survival rates than those in the highest tertile (P = 0.014; log-rank test). Conclusion Low L3-SMI is an independent risk factor for the development of infections and significantly influences the long-term survival in ACLF patients.